Autyzm relacyjnie, czyli praca na i nad kontaktem z dziećmi z zaburzeniami ze spektrum autyzmu - Gołaska, Paulina (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Relational approach to autism is a specific way of understanding needs of the child with development disorders based on three strong fundaments – psychoanalysis, development psychology and psychopathology. It is a result of complex research of typical development and identification of caretaker’s intuitive reactions, which support the child best and in a natural way. Relational therapy is not a remedy for every issue in autism. However, it should be an important, central element of a good-enough, holistic educational and therapeutic program. An introduction to other, educational-oriented activities, like learning which is a dyadic process of interaction between two people of whom one is always a teacher for another. Connection and relation should be an essence of every intervention dedicated to autistic children to, as a result, make the autism thaw.